Studi Komparatif Metode Pembuatan Teh Kombinasi Bunga Mawar dan Daun Kelor Terhadap Kadar Antioksidan dan Vitamin C Teh - Vina Nuri Sagita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the effect of two methods of making tea, a combination of rose flowers and Moringa leaves, on antioxidant and vitamin C levels in tea. Experimental method with a completely randomized design with 1 factor which includes the method of making tea with 3 repetitions. Data analysis of antioxidant levels and vitamin C used the Independent Sample T-test, while qualitative data, namely pH values ​​and physical properties, were analyzed descriptively qualitatively. The results showed that the antioxidant content in treatment P1 was 44.89% while treatment P2 was 43.62%. The vitamin C content of treatment P1 was 34.62 mg/100g while treatment P2 was 33.24 mg/100g. In conclusion, antioxidant and vitamin C levels in treatment P1 were higher than treatment P2. Keywords: Antioxidants, Roses, Moringa Leaves, Drying Methods, Vitamin C